Academic Profession and Doctoral Training. The Argentine case in the framework of the international study APIKS (Praxis Educativa, 2021)
Doctoral training is presented as one of the aspects that constitutes the academic profession as an object of study. Although the possession of a doctorate is not a general condition among Argentine academics, today it continues to be one of the most important professional and educational credentials in the labor field at the university level. The article that we present describes the main links that are intertwined between said doctoral training and the national academic profession based on the data obtained in the framework of the international APIKS (Academic Profession in the Knowledge-Based Society) research that is being carried out in more than 30 countries on all continents. The research methodology involved conducting a selfadministered survey to a representative sample of professors from national universities, whose data allow a statistical approach to the main features of the academic profession in our country.
Keywords: higher education; academic profession; postgraduate; doctoral training; APIKS Argentina.